Magnetic resonance elastography for estimating in vivo stiffness of the abdominal aorta using cardiac‐gated spin‐echo echo‐planar imaging: a feasibility study. (6th October 2020) - Dong, Huiming; Jin, Ning; Kannengiesser, Stephan; Raterman, Brian; White, Richard D.; Kolipaka, Arunark
Abstract : Introduction: Magnetic resonance elastography (MRE)‐derived aortic stiffness is a potential biomarker for multiple cardiovascular diseases. Currently, gradient‐recalled echo (GRE) MRE is a widely accepted technique to estimate aortic stiffness. However, multi‐slice GRE MRE requires multiple breath‐holds (BHs), which can be challenging for patients who cannot consistently hold their breath. The aim of this study was to investigate the feasibility of a multi‐slice spin‐echo echo‐planar imaging (SE‐EPI) MRE sequence for quantifying in vivo aortic stiffness using a free‐breathing (FB) protocol and a single‐BH protocol. Method: On Scanner 1, 25 healthy subjects participated in the validation of FB SE‐EPI against FB GRE. On Scanner 2, another 15 healthy subjects were recruited to compare FB SE‐EPI with single‐BH SE‐EPI. Among all volunteers, five participants were studied on both scanners to investigate the inter‐scanner reproducibility of FB SE‐EPI aortic MRE. Bland‐Altman analysis, Lin's concordance correlation coefficient (LCCC) and coefficient of variation (COV) were evaluated. The phase‐difference signal‐to‐noise ratios (PD SNR) were compared. Results: Aortic MRE using FB SE‐EPI and FB GRE yielded similar stiffnesses (paired t ‐test, P = 0.19), with LCCC = 0.97. The FB SE‐EPI measurements were reproducible (intra‐scanner LCCC = 0.96) and highly repeatable (LCCC = 0.99). The FB SE‐EPI MRE was also reproducible across different scanners (inter‐scanner LCCC = 0.96). Single‐BH SE‐EPI scans yielded similar stiffness to FB SE‐EPI scans (LCCC = 0.99) and demonstrated a low COV of 2.67% across five repeated measurements. Conclusion: Multi‐slice SE‐EPI aortic MRE using an FB protocol or a single‐BH protocol is reproducible and repeatable with advantage over multi‐slice FB GRE in reducing acquisition time. Additionally, FB SE‐EPI MRE provides a potential alternative to BH scans for patients who have challenges in holding their breath. Abstract : MRE‐derived aortic stiffness is a potential biomarker for multiple cardiovascular diseases. However, conventional GRE MRE requires multiple breath‐holds, which can be challenging for patients. Our study demonstrates the feasibility of in vivo multi‐slice SE‐EPI aortic MRE using a free‐breathing protocol and a single breath‐hold protocol. Free‐breathing SE‐EPI MRE provides a potential alternative to breath‐hold scans for patients who cannot hold their breath.